La communauté thérapeutique du pénitencier de Donnacona : un an déjà ! - Turcotte, Lise (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
It was in 1987 that the program for the treatment of drug addiction was started at the Donnacona Penitentiary, based on the Therapeutic Community model. It was one of the regional initiatives taken under the National Anti-Drug campaign launched in the spring of 1987. This program is to be the major regional undertaking in Quebec in the field of antidrug programs in the prison milieu.In this article, we discuss the program as it is applied at Donnacona and the persons who work there as counsellors.We then draw a general criminological profile of the inmates that are following the program and the results obtained.Finally, we mention some of the strong points of the program and some of its limitations or difficulties in applying this model in the prison milieu.